2017
DOI: 10.1016/j.heliyon.2017.e00236
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of women’s external locus of control: Associations with characteristics of their parents and their early childhood

Abstract: Locus of control (LOC) measures individuals’ expectancies regarding their ability to affect what happens to them based on how they behave. The more they believe their behaviour has something to do with what happens to them the more internal they are. In contrast the more they perceive that what happens to them is beyond their control and determined by luck, fate, chance or powerful others the more external they are. Copious research findings suggest that external LOC (ELOC) is associated with many adverse pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…The analyses used six different mutually distinct groupings, those providing the greater GOF were features of the parents and of early childhood ( Table 5). We have shown elsewhere that a combination of these two groups of variables increased the GOF to 6.89 ( Golding et al , 2017); in Table 5 we show that each addition of the various measures increased the GOF, implying that all facets had a role to play in determining ELOC.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The analyses used six different mutually distinct groupings, those providing the greater GOF were features of the parents and of early childhood ( Table 5). We have shown elsewhere that a combination of these two groups of variables increased the GOF to 6.89 ( Golding et al , 2017); in Table 5 we show that each addition of the various measures increased the GOF, implying that all facets had a role to play in determining ELOC.…”
Section: Discussionmentioning
confidence: 64%
“…In our earlier paper we showed that there were aspects of early childhood (birth to 5 years) that were independently associated with the women’s ELOC ( Golding et al , 2017). These comprised year of birth, whether they were born in Avon, breast fed (protective), had a birthmark, had at least two older siblings and whether their father was present in the household ( Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations